PPAR-α Modulators as Current and Potential Cancer Treatments - Tan, Yan; Wang, Mina; Yang, Ke; Chi, Tiange; Liao, Zehuan; Wei, Peng (Frontiers in Oncology, 2021)
Cancer is one of the leading causes of mortality worldwide. PPAR modulators may hold great potential for the management of cancer patients. Indeed, PPARs are critical sensors and regulators of lipid, and they are able to promote eNOS activation, regulate immunity and inflammation response, and affect proliferation and differentiation of cancer cells. Cancer, a name given to a cohort of diseases, is characterized by multiple distinctive biological behaviors, including angiogenesis, abnormal cell proliferation, aerobic glycolysis, inflammation, etc. In the last decade, emerging evidence has shown that PPAR-α, a nuclear hormone receptor, can modulate carcinogenesis via exerting effects on one or several characteristic pathological behaviors of cancer. Therefore, the multi-functional PPAR modulators have substantial promise in various types of cancer therapies. This review aims to consolidate the functions of PPAR-α, as well as discuss the current and potential applications of PPAR-α agonists and antagonists in tackling cancer.